Preliminary investigations for studying the effects of low carbohydrate high fat diets on gluconeogenesis in type 2 diabetes patients - Webster, Christopher (Department of Human Biology, 2020)
Type 2 diabetes (T2D) is currently one of the major health challenges across the globe. Lifestyle changes are a key component of T2D management and there is growing interest in low carbohydrate high fat (LCHF) diets as a potential dietary strategy to improve glycaemic control, reduce T2D medication requirements, and improve body weight and lipid profiles. However, carbohydrate restriction is controversial. Results from observational studies generally do not support the food choices associated with carbohydrate restriction while results from short-term randomised controlled trials (RCTs) are more likely to show significant benefits of LCHF diets. Additionally, both study designs have limitations and opinion on LCHF diets is polarised due to ambiguities in how to interpret the available data. Chapter 1 of this thesis reviews the impact of prospective cohort studies, randomised controlled trials, and dietary policies on current opinions towards LCHF diets for the management of T2D. Uncertainty over the safety of LCHF diets remains a concern and additional observational studies and short-term RCTs of the same quality as existing research are unlikely to add any further clarity. For this reason, research focused on understanding the underlying mechanisms of carbohydrate restricted diets may be an alternative approach to alleviate or validate some of the concerns being expressed about LCHF diets. One such mechanism is the dysregulation of glucose production via gluconeogenesis, which is a key pathology of T2D but which has been incompletely studied. Indeed, the effects of LCHF eating on gluconeogenesis in T2D patients has not yet been studied, nor has gluconeogenesis been investigated in the context of T2D remission. This is an area of interest for future research and the aim of this thesis was to conduct preliminary studies to prepare the groundwork for such studies. There is large heterogeneity in the low carbohydrate diets that have been prescribed in controlled trials and the composition and characteristics of the LCHF diets that patients are finding effective in the real world is unknown. Study 1 (Chapter 2 of this thesis) aimed to better understand the LCHF diet by investigating the diet, diabetes status, and personal experiences of T2D patients who had self-selected and followed an LCHF diet of their own accord. This study was a multi-method investigation which consisted of quantitative assessments of diet and diabetes status, as well as in-depth interviews which were analysed using qualitative methods. Results from this study will be used to inform design and protocol decisions in future controlled trial studies. Study 2 (Chapter 3 of this thesis) piloted the use of stable isotope tracers for the quantification of endogenous glucose production and gluconeogenesis in the early postabsorptive state (5 hours after a meal). For methodological reasons, prior investigations have usually measured gluconeogenesis after an overnight fast and therefore, little is known about the effects of dietary composition on gluconeogenesis within the early post-absorptive state. Study 2 quantifies gluconeogenesis 5 hours after a meal and the validity of the data is discussed. Finally, Chapter 4 outlines future perspectives for research based on findings from Chapter 2 and Chapter 3.